Regulators Of Meiotic Cell Division Of The Growing Oocytes - SUBHABRATA MOITRA; SUBHASHIS SAHU (International Journal of Pharma and Bio Sciences, 2010)
The growth of vertebrate oocyte stops temporarily at the late diplotene stage of 1st meiotic cell division and stays at that stage until puberty. Before ovulation, the arrest is resumed and enters the 2nd meiotic phase and stops again at the metaphase until fertilization. The arrest is mediated by the constant flow of cAMP, which is generated by activated adenylyl cyclase. This state is manifested by the presence of the intact nuclear envelope (NE) or germinal vesicle (GV). When the flow of cAMP is reduced, the arrest resumes followed by the breakdown of nuclear envelop/germinal vesicle (NEBD/GVBD). Studies reveal that various control factors regulate the entire process. Cyclin dependent kinases (CDKs), A kinase anchoring protein (AKAP) and the CDC2/SPDY complex have been shown to play vital roles in that mechanism. The connexin proteins between granulosa cells and oocyte remain opened during arrest and close after the LH surge to resume the arrested meiosis. Recent data indicate the correlation of a newly discovered protein Aurora Kinase A (AURKA) in the regulation of the cell cycle events of the oocyte. Here, we tried to present a synopsis of the major regulatory factors that control the entire morphological cycle of a growing oocyte, in vivo.